Captive environment induced greater physiological changes than probiotic treatment in Pelophylax nigromaculatus - Ji-Eun Lee; Yuno Do; Jun-Kyu Park (PLoS ONE, 2026)
Ex situ conservation of amphibians is an effective countermeasure against various threats to populations in situ ; however, it may entail physiological and ecological challenges that decrease individual fitness. We examined changes in the fecal bacterial community and physiological status of black-spotted pond frogs ( Pelophylax nigromaculatus ) during their transition from wild to captive environments. Additionally, we aimed to improve the physiological status and shift the fecal bacterial community through probiotic treatment. A change in fecal bacterial composition was observed after the transition from the wild to captivity and after administering probiotic treatment, whereas fecal bacterial diversity remained unchanged by environmental change and probiotics. Contrary to our expectations, changes in fecal bacterial composition did not affect innate immunity and body composition with regard to fat and lean mass and bone mineral density. Transition to the captive environment, rather than the probiotic treatment, elicited significant changes in plasma biochemical components, allowing us to predict potential issues associated with the captive environment. Our results showed that although probiotic treatment can alter the bacterial community in P. nigromaculatus , the specific probiotic treatment used in this study did not improve host physiology, at least in the short term. Additionally, some problems may occur even in a standard captive husbandry condition, which can be effectively monitored through physiological examination and monitoring. We suggest that a holistic approach be adopted to create captive environments informed by the ecology and physiology of the species and a thorough understanding of host-microbe interactions.